Perceptions of police-juvenile contact predicts self-reported offending in adolescent males - Walsh, Hannah (Psychology, crime & law, 2019)
Evidence suggests that positive experiences with the police can foster attitudes of respect towards the justice system that can reduce an adolescents’ propensity to commit later illegal behaviors. To advance prior work, we tested whether this association might be stronger for those adolescents who associate with deviant peers. Additionally, we tested whether the link between attitudes towards police and the justice system, and the influence of peer delinquency, would be weaker for those with elevated callous-unemotional (CU) traits. These predictions were examined in a prospective study using a sample (N = 1,216) of adolescent males who were followed prospectively for 2 years following their first official contact with the juvenile justice system. Positive experiences with the police following the youth’s first arrest were associated with less self-reported delinquency 2 years later, which was partially mediated by reductions in adolescents’ cynicism about the legal system. However, this link was only significant for youth with low levels of peer delinquency. Although CU traits were related to less positive perceptions of experiences with the police and greater cynicism about the justice system, CU traits did not moderate the associations among experiences, attitudes, and later illegal behavior nor did they moderate the influence of peer delinquency.